Maternal pregnancy-related anxiety and children's physical growth: the Ma'anshan birth cohort study - Jixing Zhou; Shanshan Zhang; Yuzhu Teng; Jingru Lu; Yufan Guo; Shuangqin Yan; Fangbiao Tao; Kun Huang (BMC, 2023)
Abstract Background Epidemiological studies have identified maternal antenatal anxiety and several adverse birth outcomes, but limited studies have focused on the relationship with the long-term physical growth of children. The study aimed to assess the influence of maternal pregnancy-related anxiety on physical growth in children at different exposure periods during pregnancy. Methods 3,154 mother-child pairs were included based on the Ma'anshan birth cohort study. Maternal prenatal anxiety was obtained by administering a questionnaire using the pregnancy-related anxiety questionnaire (PRAQ) scale during the 1st, 2nd and 3rd trimesters of pregnancy. Body fat (BF) (48 to 72 months) and Body Mass Index (BMI) (birth to 72 months) were collected repeatedly for children. Group-based trajectory models were applied to fit the different trajectories of BMI and BF. Results Maternal anxiety in the 2nd (OR = 0.81; 95% CI: 0.68 to 0.98; P < 0.025) and 3rd (OR = 0.80; 95% CI: 0.67 to 0.97; P = 0.020) trimesters was associated with a decreased risk of rapid weight gain (RWG) in the first year of life. Children aged 48 to 72 months of mothers with anxiety in the 3rd trimester had lower BMI (β = -0.161; 95% CI, -0.293 to -0.029; P = 0.017) and BF (β = -0.190; 95% CI, -0.334 to -0.046; P = 0.010), and these children were less likely to develop a very high BMI trajectory (OR = 0.54; 95% CI: 0.34 to 0.84; P = 0.006), and a high BF trajectory (OR = 0.72; 95% CI: 0.53 to 0.99; P = 0.043). Similar associations were found between maternal anxiety in both 2nd and 3rd trimesters and children's physical growth. Conclusions Offspring of mothers with prenatal anxiety in the 2nd and 3rd trimesters predicts poorer growth in infancy and preschool age. Early improvement and treatment of prenatal anxiety could benefit physical health and development in early childhood.